Observation of a superconducting state of a topological superconductor candidate, FeTe0.6Se0.4, equipping ferromagnetic electrodes with perpendicular magnetic anisotropy. (24th August 2021) - Ohnishi, Kosuke; Gupta, Sachin; Kasahara, Shigeru; Kasahara, Yuichi; Matsuda, Yuji; Shigematsu, Ei; Ohshima, Ryo; Ando, Yuichiro; Shiraishi, Masashi
Abstract: Iron selenide telluride, FeTeSe, is an attractive layered material for both superconductivity and spintronics applications. FeTeSe enables Ising-type superconductivity, which involves spin-momentum locking. We report superconductivity of mechanically exfoliated thin film FeTe0.6 Se0.4 that equips ferromagnetic electrodes with perpendicular magnetic anisotropy to detect possible Ising spin paring. The superconducting transition is observed at T  = 15 K. More importantly, the upper critical field of FeTe0.6 Se0.4 is anisotropic and the in-plane upper critical field is measured to be 145 T. These results show that the superconductivity of thin film FeTe0.6 Se0.4 is robust and FeTe0.6 Se0.4 can be a potential material stage for super-spintronics.